Provision of Multi-Nutrient Block for Local Goats: Effects on Physico-Chemical Properties of Goat Milk - Nasir, Asmuddin; Dagong, M. I. A.; Mide, M. Zain; Islamiyati, R.; Irwan, M.; Basri, H. (Proceeding INTERNATIONAL SEMINAR IMPROVING TROPICAL ANIMAL PRODUCTION FOR FOOD SECURITY)
Farmers in Enrekang, South Sulawesi typically feed their goats with Gliricidia maculuta as a sole diet. This may cause a problem due to asynchrony of nutrient availability in the rumen,especially the availability of energy and protein, which could lead to poor milk yield in terms ofquantity and quality. The purpose of this research was to study the effect of providing multi-nutrientblock (MNB) on the physical and chemical characteristics of goat milk. Ten Ettawa crossbred goatson the 3rd-4th month of their lactating period were randomly divided into two groups (fivegoats/group). Each group was either fed on Gliricidia maculata/control (ration C, a ration typicallyused by Enrekang farmers for feeding their goats) or fed on C + MNB (CM). MNB was formulatedfrom locally available feedstuff and was provided at the level of approximately 500 g/head/d. Theresults of the study showed that provision of MNB did not significantly (P>0.05) improve milk yield,i.e. 198 and 274 ml/d for C and CM, respectively. The treatment did not significantly (P>0.05) affectphysical characteristics, i.e. pH and specific gravity of the milk. Similarly, provision of MNB did notsignificantly (P>0.05) alter chemical composition, i.e. total solids, crude protein, fat, carbohydrate,lactose, mineral, Ca, and P of the milk.  In conclusion, there was no significant benefit on providingmulti-nutrient block for goats consuming Gliricidia maculuta as a sole diet in terms of physical andchemical properties of the milk, but there was a tendency that provision of MNB may improve yield,crude protein and fat of goat milk.Key Words: Multi-Nutrient Block, Protein of Goat Milk, Fat of Goat Milk, Total Solids of Goat Milk, Gliricidia maculata